To what extent asymmetric information influences Private Equity-backed firms’ performance in the UK in case of the IPO exit? - Solomatin, Dmitry (2011)
The objective of this study is to analyse the performance of private equity-backed initial public offerings (IPOs) in the UK for the period from 1990 to 2010 in the light of asymmetric information which takes place between the IPO companies and investors. This analysis covers two complete market cycles in the stock market, and consequently two waves of IPOs and provides the information on two performance characteristics: short-term returns represented by underpicing which is the proxy of informational asymmetry by assumption, and long-term returns which are determined by the period of up to three years after the IPO. Additional insights are gained by exploring the relevance of certain characteristics of management buyouts (MBOs) and the magnitude of underpricing. For this, the underpricing has been assessed from different angles. First, the underwriter reputation has been examined when firms are grouped according to the ranking which placed the MBOs in three sub-groups with high rank underwriters, middle rank and low rank private equity firms. Then the market capitalization has been used to evaluate the impact of this proxy on the magnitude of underpricing. Similarly, the IPO companies are grouped on the size basis and three sub-groups are organized with the small size companies, the middle size and the large size MBOs. Finally, the investment duration has been analysed in order to find out whether it influences the underpricing. For this, the MBOs are divided into three categories depending on the length of time during which the private equity investor stays invested. The IPO companies in which investments have been made for the period less than two years, between two and five years and more than five years. The empirical findings provide significant evidence that private equity-backed IPOs generate positive initial returns in a set of 103 MBOs for the period from 1990 to 2010. In fact, the private equity firms profit first from the underpricing which is short-run returns and second from hold-and-buy returns which are considered as long-run returns. In average, for the aggregate sample of MBOs, the underpricing accounts for 6.5%. The long-term returns for the aggregate sample are around 31% for the period of three years after the IPO. This figure is not significantly different to the market index for the same period. However between the second and the third year of investment, for the sub-group of underpriced MBOs considerably outperforms the market index with the peak at 27% of abnormal returns. Further analysis of aspects that may determine the underpricing reveals that the reputation of the underwriter is negatively correlated with the underpricing. The high ranking sub-group shows significantly less underpricing than other two sub-groups. In addition, the market capitalization has also impact on the underpricing with the negative correlation. In contrast, only the sub-group of small MBOs shows considerable difference in the results compared to other peers. Two other categories do not demonstrate remarkable differences. The third contributor to the magnitude of underpricing which is related to the duration of the investment also indicates the strong negative relationship with the underpricing. It implies that those MBOs that are stayed invested for the period up to two years will be seriously underpriced while IPO companies with duration of the investment between two and five years will be underpriced insubstantially. Overall, this study provides empirical evidence that private equity-backed initial public offerings in the UK generate positive returns and positive performance for the 1990 to 2010 period.